Scurvy as a Cause of Leg Pain and Limp in Pediatric and Adolescent Patients - Christopher J. DeFrancesco, MD; David Kell, BA; Sean Owens, BS; Matt Grady, MD; Naomi Brown, MD (Journal of the Pediatric Orthopaedic Society of North America)
Vitamin C deficiency (VCD) results in collagen dysfunction due to decreased lysyl and prolyl hydroxylase enzyme activity. The resulting disease, known as scurvy, can present with various findings, including gingival bleeding, bruising, other skin lesions, poor wound healing, and tooth and bone abnormalities. VCD is also an uncommon cause of musculoskeletal pain among children. This current concept review aims to summarize our institutional experience with scurvy in ten patients and compare it with existing literature. Astute history taking, critical review of imaging, thorough physical examination, and a high index of suspicion are essential to efficiently diagnose scurvy in the child presenting with nonspecific lower extremity pain or limping. In these patients, a simple question about diet when taking the history could help focus the differential diagnosis and prevent the need for unnecessary imaging, anesthetic events, invasive diagnostic procedures, and prolonged pain and symptoms. Key Concepts: (1) Scurvy, the condition caused by vitamin C deficiency, is not a historical disease, with research suggesting that its incidence in the US is on the rise. (2) Scurvy can result in lower extremity pain and limping among children, who may present for orthopaedic evaluation. (3) An increased index of suspicion for vitamin C deficiency should be maintained for any child with a history of restrictive eating, especially those with a history of autism spectrum disorder. (4) Orthopaedic providers should know the specific MRI and x-ray findings characteristic of vitamin C deficiency. (5) Vitamin C levels can be repleted in weeks with proper supplementation, but children with scurvy due to restrictive eating generally require continued intervention from nutrition and/or feeding specialists.